Simplifying
(9x + -12) + -1(5x + -7) = 0
Reorder the terms:
(-12 + 9x) + -1(5x + -7) = 0
Remove parenthesis around (-12 + 9x)
-12 + 9x + -1(5x + -7) = 0
Reorder the terms:
-12 + 9x + -1(-7 + 5x) = 0
-12 + 9x + (-7 * -1 + 5x * -1) = 0
-12 + 9x + (7 + -5x) = 0
Reorder the terms:
-12 + 7 + 9x + -5x = 0
Combine like terms: -12 + 7 = -5
-5 + 9x + -5x = 0
Combine like terms: 9x + -5x = 4x
-5 + 4x = 0
Solving
-5 + 4x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '5' to each side of the equation.
-5 + 5 + 4x = 0 + 5
Combine like terms: -5 + 5 = 0
0 + 4x = 0 + 5
4x = 0 + 5
Combine like terms: 0 + 5 = 5
4x = 5
Divide each side by '4'.
x = 1.25
Simplifying
x = 1.25